2017
DOI: 10.1038/srep43290
|View full text |Cite
|
Sign up to set email alerts
|

Hyodeoxycholic acid derivatives as liver X receptor α and G-protein-coupled bile acid receptor agonists

Abstract: Bile acids are extensively investigated for their potential in the treatment of human disorders. The liver X receptors (LXRs), activated by oxysterols and by a secondary bile acid named hyodeoxycholic acid (HDCA), have been found essential in the regulation of lipid homeostasis in mammals. Unfortunately, LXRα activates lipogenic enzymes causing accumulation of lipid in the liver. In addition to LXRs, HDCA has been also shown to function as ligand for GPBAR1, a G protein coupled receptor for secondary bile acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 44 publications
4
47
0
Order By: Relevance
“…26 In the present case, we performed docking calculations on the most potent compound of the series 1 in the receptor homology model of GPBAR1 that has been successfully used in our previous drug design studies. 13b, 18,19,20 The docking results showed that 1 binds to GPBAR1 similarly to other BA compounds previously investigated by us as agonists of this receptor (Fig. 7).…”
Section: Molecular Modelingsupporting
confidence: 73%
See 4 more Smart Citations
“…26 In the present case, we performed docking calculations on the most potent compound of the series 1 in the receptor homology model of GPBAR1 that has been successfully used in our previous drug design studies. 13b, 18,19,20 The docking results showed that 1 binds to GPBAR1 similarly to other BA compounds previously investigated by us as agonists of this receptor (Fig. 7).…”
Section: Molecular Modelingsupporting
confidence: 73%
“…HDCA was transformed in the C-23 protected aldehyde 13 following our previously published procedure. 18,22 Wittig olenation and double bond epoxidation in the same operative conditions described for the preparation of derivatives 1 and 2, gave the corresponding nor derivatives 5 and 6.…”
Section: Chemistrymentioning
confidence: 92%
See 3 more Smart Citations